2012
DOI: 10.1210/me.2011-1208
|View full text |Cite
|
Sign up to set email alerts
|

Palmitoylation Regulates 17β-Estradiol-Induced Estrogen Receptor-α Degradation and Transcriptional Activity

Abstract: The estrogen receptor-α (ERα) is a transcription factor that regulates gene expression through the binding to its cognate hormone 17β-estradiol (E2). ERα transcriptional activity is regulated by E2-evoked 26S proteasome-mediated ERα degradation and ERα serine (S) residue 118 phosphorylation. Furthermore, ERα mediates fast cell responses to E2 through the activation of signaling cascades such as the MAPK/ERK and phosphoinositide-3-kinase/v-akt murine thymoma viral oncogene homolog 1 pathways. These E2 rapid eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
143
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 106 publications
(160 citation statements)
references
References 42 publications
15
143
1
1
Order By: Relevance
“…S5D). Thus, although previous in vitro experiments suggested that ERα palmitoylation influences the abundance of the receptor protein (22), this was not detected in vivo in arteries and uterus.…”
Section: Wt-c451contrasting
confidence: 57%
See 3 more Smart Citations
“…S5D). Thus, although previous in vitro experiments suggested that ERα palmitoylation influences the abundance of the receptor protein (22), this was not detected in vivo in arteries and uterus.…”
Section: Wt-c451contrasting
confidence: 57%
“…We first determined whether mutation of the palmitoylation site of mouse ERα alters the expression level of the protein in vivo, because in vitro studies (22) had shown that such a mutated human ERα (C447A) was more sensitive to E2-dependent degradation. The mutated C451A-ERα protein was normal in abundance in the different murine tissues analyzed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Par ailleurs, cette signalisation d'origine membranaire peut également moduler l'activité transcriptionelle d'ER via l'activation de kinases qui phosphorylent le récepteur nucléaire et modulent ainsi son activité nucléaire [34]. En ce qui concerne l'étude de la conformation de l'ER membranaire, la topologie du récepteur associé avec la membrane plasmique n'en est encore qu'à ses balbutiements.…”
Section: Ils Induisent Des Voies De Signalisation Différentes Comme Lunclassified